Analisis Efisiensi Produksi Padi Anorganik di Kecamatan Rakit Kulim Kabupaten Indragiri Hulu - Fris Safal; Syaiful Hadi; Jumatri Yusri (Journal of Agribusiness and Community Empowerment (JACE), 2019)
Rice is an important commodity because  it is a staple food source for almost all Indonesian people. One way to increase rice production is by using available resources more efficiently. The use of production factors such as land, seeds, fertilizers, pesticides and labor will affect the total production of rice produced. This study aims to determine the technicality of inorganic rice cultivation, calculate production costs and analyze the efficiency of inorganic rice farming production in the District of Rakit Kulim. The analytical method used is descriptive analysis, farming cost analysis and DEA (Data Envelopment Analysis) analysis. The number of samples is 40 inorganic rice farmers. The results showed that the inorganic rice cultivation technique in the District of Rakit Kulim was not in accordance with the recommendations. Incompatibility is caused by the unavailability of technical books for inorganic rice cultivation from the localita specific crop study center. The total cost of producing inorganic rice farming in the District of Rakit Kulim is Rp. 23,622,481, - / Ha. While the average income is Rp. 24,230,168, - / Ha with a net income of 607,687, - / Ha with an RCR value of 1.07. The results of the analysis of production efficiency using DEA show that the proportion of technically efficient farmers is 50percents with an average value of 0.946. The proportion of efficient farmers is allocatively relatively small at 32.5percents with an average value of 0.975. Economic efficiency is relatively small at 32.5percents with an average value of 0.927.